The Mediating Role of Learning Motivation: A Structural Equation Model of Student Learning Outcomes - Andi Sessu; Besse Arnawisuda Ningsi; Irvana Arofah (IJBLE Scientific Publications Community Inc., 2026)
Student learning outcomes are shaped by both individual motivational processes and the academic environment. This study examined the direct and indirect associations among learning interest, campus environment, learning motivation, and student learning outcomes. Data were obtained from 172 students in the Faculty of Economics and Business at Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, and analyzed using partial least squares structural equation modeling. The structural results showed that learning interest was not directly associated with learning outcomes (β = −.177, p = .062), but it was positively associated with learning motivation (β = .511, p < .001). Campus environment was positively associated with both learning outcomes (β = .325, p = .001) and learning motivation (β = .444, p < .001), while learning motivation was positively associated with learning outcomes (β = .265, p = .029). Learning motivation significantly mediated the relationships between learning interest and learning outcomes (β = .135, p = .035) and between campus environment and learning outcomes (β = .118, p = .048). The model explained 67.4% of the variance in learning motivation but only 20.3% of the variance in learning outcomes. These findings indicate that interest is more likely to translate into academic outcomes when it is accompanied by sustained motivation, whereas a supportive campus environment contributes through both direct and motivational pathways. The findings should nevertheless be interpreted cautiously because the reported cross-loading matrix contains a discriminant-validity anomaly that requires verification against the original PLS output.